Liquidity Ratio Analysis to Assess the Financial Performance of PT Mayora Indah Tbk - Modamba, Widya; Lamuda, Ilyas; Hasan, Wahyudin; Yakup, Anggita Permata (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
This study's background is based on previous studies that show variations in the assessment of the company's financial performance. Therefore, this study was conducted to provide a clearer picture of the company's ability to meet its short-term obligations. The research method used is descriptive analysis with a quantitative approach, where the data obtained is classified, explained, and analyzed using liquidity ratios, namely the Current Ratio, Quick Ratio, and Cash Ratio. The data used are the financial statements of PT. Mayora Indah Tbk for the last five years. The study results show that the Current Ratio, Quick Ratio and Cash Ratio have sufficient cash to meet their short-term obligations. Based on the results of this analysis, it can be concluded that PT. Mayora Indah Tbk has good liquidity and can meet its short-term obligations during the study period. Thus, the initial hypothesis stating that the company's liquidity ratio is in poor condition is rejected.